2018
DOI: 10.1155/2018/8406187
|View full text |Cite
|
Sign up to set email alerts
|

Student Evaluations of a (Rude) Spoken Dialogue System Insights from an Experimental Study

Abstract: Communicating with spoken dialogue systems (SDS) such as Apple’s Siri® and Google’s Now is becoming more and more common. We report a study that manipulates an SDS’s word use with regard to politeness. In an experiment, 58 young adults evaluated the spoken messages of our self-developed SDS as it replied to typical questions posed by university freshmen. The answers were either formulated politely or rudely. Dependent measures were both holistic measures of how students perceived the SDS as well as detailed ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
3
0
2
Order By: Relevance
“…The finding that politeness was less of a concern in expert situations than in general service situations (Experiment 1 in this study, Inbar and Meyer, 2019;Rea et al, 2021) indicates that the robot design of politeness should be more effective in general service situations than in expert situations. As studies proposing personalize agents' politeness levels according to each participant (Firdaus et al, 2022;Smith et al, 2022), participants' demographic differences (e.g., age and gender) may affect politeness impressions (Jucks et al, 2018;Kumar et al, 2022;Miyamoto et al, 2019;Rana et al, 2021;Zhu andKaber, 2012, but not observed in Inbar andMeyer, 2015;Inbar and Meyer, 2019;Lee et al, 2019). As this study did not aim to investigate demographic differences, we did not control the numbers of male and female participants and participants' ages, but conducted a posteriori analysis regarding gender differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding that politeness was less of a concern in expert situations than in general service situations (Experiment 1 in this study, Inbar and Meyer, 2019;Rea et al, 2021) indicates that the robot design of politeness should be more effective in general service situations than in expert situations. As studies proposing personalize agents' politeness levels according to each participant (Firdaus et al, 2022;Smith et al, 2022), participants' demographic differences (e.g., age and gender) may affect politeness impressions (Jucks et al, 2018;Kumar et al, 2022;Miyamoto et al, 2019;Rana et al, 2021;Zhu andKaber, 2012, but not observed in Inbar andMeyer, 2015;Inbar and Meyer, 2019;Lee et al, 2019). As this study did not aim to investigate demographic differences, we did not control the numbers of male and female participants and participants' ages, but conducted a posteriori analysis regarding gender differences.…”
Section: Discussionmentioning
confidence: 99%
“…As studies proposing personalize agents’ politeness levels according to each participant ( Firdaus et al, 2022 ; Smith et al, 2022 ), participants’ demographic differences (e.g., age and gender) may affect politeness impressions ( Jucks et al, 2018 ; Kumar et al, 2022 ; Miyamoto et al, 2019 ; Rana et al, 2021 ; Zhu and Kaber, 2012 , but not observed in Inbar and Meyer, 2015 ; Inbar and Meyer, 2019 ; Lee et al, 2019 ). As this study did not aim to investigate demographic differences, we did not control the numbers of male and female participants and participants’ ages, but conducted a posteriori analysis regarding gender differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os resultados indicaram que os alunos do grupo da agente amigável apresentaram um maior engajamento e ganho de aprendizado, confirmando as avaliações de outros trabalhos daárea [Jucks et al 2018, Guo and Goh 2015, McLaren et al 2011. Também houve uma maior intensidade de emoções positivas nos alunos que utilizaram as agentes amigável e direta.…”
Section: Conclusãounclassified
“…Existem uma série de trabalhos que buscaram verificar a eficiência de APAs com atitudes empática, polida, rude e com rapport 1 no aumento da aprendizagem e engajamento dos alunos [Jucks et al 2018, Hastie et al 2016, Krämer et al 2016, e alguns estudos também analisaram o impacto desses agentes nos estados afetivos dos alunos [Moridis andEconomides 2012, Wang et al 2010]. Entretanto, esses trabalhos não compararam os efeitos de agentes pedagógicos animados com atitudes opostas (como a educação e a rudeza, por exemplo) e neutras (sem emoções), e não consideraram o estado de ansiedade dos estudantes.…”
Section: Introductionunclassified